Teacher’s Strategies in Controlling Students’ Misbehavior During Learning Process - Riri Aryana; Armilia Riza; Elmiati Elmiati (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the types of students' misbehavior in class XI IPS at SMAN 2 Pulau Punjung and the strategies used by teachers to control them. This research is a descriptive research. The participants in this study were students of grade XI IPS and one English teacher who taught the class. To collect data, researcher used instruments, such as video recording, observation checklist, field note and interview. Researcher obtained data about any misbehavior that class XI IPS students did, as well as strategies that were often used by teacher in controlling students who did misbehavior. Based on the results of data analysis, the researcher concluded that the misbehavior committed by students in grade XI IPS was categorized into active and passive misbehavior. And of the 4 types of strategies that the researchers studied, the teacher used 2 types of strategies, namely pre-empting student misbehavior and using reprimand.